FRI0206 Abatacept (CTLA4-IG) suppresses T cell activation and reduces TH17 cells as well as plasma IL-6 in patients with rheumatoid arthritis. (23rd January 2014) - Matsutani, T.; Li, Y.; Murakami, M.; Lee, H.-M.; Aoki, C.; Sekiguchi, M.; Matsui, K.; Kitano, M.; Namiki, M.; Ohmura, K.; Murakami, K.; Fujii, T.; et al.
Abstract : Background: Abatacept (CTLA4-Ig) controls RA via competitive inhibition of CD28 binding to CD80/CD86 ligands. However, the mechanism of action of abatacept in human remains inadequately understood. Objectives: To elucidate how abatacept treatment achieves therapeutic effect on RA, we examined alterations of T cell phonotypes, T cell subsets, and plasma cytokine profiles in RA patients during abatacept treatment. Methods: PBMCs and plasmas were collected from healthy individuals (HI, n=15) and RA patients before (RA-0M, n=45) and 6 months after treatment (RA-6M, n=25). Paired data from identical patients were included (n=24). Surface phenotypes (CD3, CD4, CD8, CD28, CD45RO) and activation markers (CD25, CD69, CD62L - ) of T cells were analyzed with FACS. Treg cells (CD4 + CD25 + Foxp3 + ) were measured with intracellular staining with anti-Foxp3 antibody. After in vitro stimulation with PMA/Ionomycin, cells were intracellularly stained with anti-IFN-γ, anti-IL-4 or anti-IL-17A antibodies. The plasma levels of IL-2, IL-4, IL-6, IL-10, IFN-γ, TNF were measured using bead-based cytometric bead array. Changes in the proportions of T cell subsets and the plasma cytokine levels were examined between before and 6 months after abatacept treatment. Statistical analyses were done using one-way ANOVA (multiple tests) or Wilcoxon matched paired test (paired data). Results: There were little differences of proportion of CD25 + on CD4 + between RA and HI. However, the proportion and the mean fluorescent intensity of CD25 significantly decreased and became significantly lower than in HI after abatacept treatment. Proportions of Treg cells (CD25 + Foxp3 + ) in CD4 + T cells and their absolute numbers were not significantly different among HI, RA-0M and RA-6M. Th1 (CD4 + IFN-γ + ) and Th2 (CD4 + IL-4 + ) cells significantly increased in RA-0M compared with HI and didn't change during treatment. Meanwhile, Th17 (CD4 + IL-17A + ) cells were significantly abundant in RA-0M than in HI and significantly reduced at 6 months after treatment. Similarly, high levels of plasma IL-6 were detected in RA-0M and significantly decreased after treatment. Conclusions: Abatacept is suggested to inhibit IL-2 dependent CD4 + T cell proliferation by decreasing the expression of CD25 (IL-2Rα). Given that naïve CD4 + cells differentiate into IL-17 producing Th17 in the presence of IL-6 and that IL-17 induces RANKL expression in osteoblast/synovial fibroblast, these results suggest the possibility that abatacept has suppressive effect on IL-6 production and Th17 differentiation, resulting in reduction of synovial inflammation and osteoclastogenesis in rheumatoid arthritic joint. Disclosure of Interest: T. Matsutani: None Declared, Y. Li: None Declared, M. Murakami: None Declared, H.-M. Lee: None Declared, C. Aoki: None Declared, M. Sekiguchi Grant/Research support from: Bristol-Myers Squibb Japan, K. Matsui: None Declared, M. Kitano Grant/Research support from: Bristol-Myers Squibb Japan, M. Namiki: None Declared, K. Ohmura Grant/Research support from: Bristol-Myers Squibb Japan, K. Murakami: None Declared, T. Fujii Grant/Research support from: Bristol-Myers Squibb Japan, T. Kuroiwa: None Declared, Y. Shimaoka: None Declared, H. Nakahara: None Declared, K. Maeda: None Declared, S. Irimajiri Grant/Research support from: Bristol-Myers Squibb Japan, M. Funauchi Grant/Research support from: Bristol-Myers Squibb Japan, Y. Imura: None Declared, T. Ikawa: None Declared, A. Nanpei: None Declared, T. Azuma: None Declared, T. Sasaki: None Declared, A. Yokota: None Declared, Y. Kawahito Grant/Research support from: Bristol-Myers Squibb Japan, T. Mimori Grant/Research support from: Bristol-Myers Squibb Japan, H. Sano Grant/Research support from: Bristol-Myers Squibb Japan, N. Nishimoto Grant/Research support from: Bristol-Myers Squibb Japan